Investigation of the expression of irisin and some cachectic factors in mice with experimentally induced gastric cancer - Altay, Diler Us; Keha, E. Edip; Yaman, Serap Ozer; Ince, Imran; Alver, Ahmet; Erdogan, Bahattin; Mentese, Ahmet (Oxford Univ Press, 2016)
Background: The purpose of this study was to determine whether irisin is secreted by gastric tumor cells experimentally induced in mice, and also if it has any effect on cancer cachexia. Design and Methods: 12 out of 60 BALB/c mice were used as a control group, while N-nitroso-N-methylurea (MNU) was administered orally to the remaining 48. After 150 days, the surviving mice were sacrificed by decapitation, blood and stomach, skeletal muscle, brown and white adipose tissue specimens were collected. Following histopathological evaluation of the stomach tissues, it was decided to create four groups, one control group and three consisting of mice administered MNU, no cancer, pre-cancer and cancer. Gene expression analyses of fibronectin type III domain containing protein 5 (FNDC5) and some cachexia-related proteins were performed in tissue samples, while levels of irisin, and various inflammatory and tumor markers together with cachectic factors were determined in serum samples. Results: The levels of inflammatory, tumor markers and cachectic factors in serum samples were significantly higher in the cancer group compared with the control group. No expression of FNDC5 or zinc-alpha-2 glycoprotein, a cachectic factor, was observed in gastric tissues from the control and MNU groups, whereas significantly increased FNDC5 expression was determined in the both white and brown adipose tissues from the cancer group. Conclusion: Increased FNDC5 expression in white and brown adipose tissues may have a cachectic effect in mice with induced cancer. However, it is not possible to explain the mechanism of the relationship between irisin and gastric cancer development on the basis of the results of this study.
Keywords: Methyl-N-Nitrosourea; Weight-Loss; Circulating Irisin; Glandular Stomach; Messenger-Rna; Brown-Fat; Obesity; Serum; White; Adipocytes